Development of Vibrator Feeding Mechanism Using Two Sets of Rollers for the Separation of Ball Grading For Industry Benefits - P. Sundar Singh Sivam, S.; Saravanan, K.; Pradeep, N.; Rajendra Kumar, S.; Mathur, Shubhang; Dingankar, Usama; Arora, Anurag (International Journal of Engineering and Technology, 2018)
The study aims to provide an Automatic Feeder Machine to inspect the Ball diameter to eliminate any parallax error and to reduce the measuring time significantly also to create an ergonomic environment for the operator. The measurement of Steel Ball diameter which is very much important needs to measure 100% before assembly. The inspection is done manually by using Micrometer which takes more time and possibility committing parallax error by operator. The micrometer needs to calibrate with master very frequently. The micrometers are normally used to measures very precision parts in rare frequency only. The possibility of mixing up rejected with acceptable items is very common in this type of inspection. The balls which are measured manually are kept separately according to the ball diameters. Due to high measurement ratio of the balls, operator by mistake passes the rejected balls in to right balls. To avoid this problem, this study focused on to develop the automatic inspection machine of vibrator feeding mechanism for balls to improve the accuracy of inspection and reduce the inspection time.Â Â